The Principal's Controlling Function Regarding the Use of Learning Media in Supporting Lifelong Learning - Rohadi, Rohadi; Syaifuddin, Muhammad; Mahnun, Nunu (Universitas Negeri Padang, 2025)
This study aims to analyze the principal's controlling function towards the use of learning media in supporting lifelong learning at SMPN 5 Bukit Tambun, Anambas Islands Regency. The background of this study is based on the importance of the principal's role as a controller of learning management who ensures that media is used effectively, innovatively, and in accordance with the needs of students in the digital era, while also facing geographical challenges and limited facilities in the archipelago region. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation, which are then analyzed through data reduction, data presentation, and drawing conclusions. The results of the discussion indicate that the principal's controlling function includes three important aspects: first, the principal's role in controlling the use of learning media through supervision, coaching, and evaluation; second, the effectiveness of the use of learning media in increasing motivation, understanding concepts, and supporting the principles of lifelong learning; and third, challenges faced such as limited infrastructure, teacher capabilities, and geographical barriers, which are overcome through strategies to improve teacher competency, routine monitoring, optimization of simple media, and collaboration with external parties. Thus, this study confirms that the principal's controlling function is not only as a supervisory instrument, but also as a key factor in realizing lifelong learning in schools.